Strategi Lebanon Dalam Meningkatkan Keamanan Ruang Siber - Maria de Liguori Sakunab, Alfonsus; Silvia , Anggraeni (Jurnal Kajian Ilmiah, 2021)
Abstract Cybersecurity has attracted attention in the study of international relations. This issue is important because most of life is connected to cyberspace. This research analyzes Lebanon's cybersecurity strategy in its official cybersecurity documents. The theoretical framework used in this study is the Three Perspective Theory of Cyber Sovereignty. The theory is explaining the division of layers in the context of sovereignty in cyberspace. The method used in this research is quantitative research obtained through the MAXQDA and GEPHI. The applications that are used in this research are to provide evidence of data in the Lebanese national strategy document. The results of this study indicate that the Lebanese security strategy documents tend to be exclusive. The Lebanese government is more dominant in discussing matters that are administrative, theoretical, principal, and planning. Keywords: Cyber Security, Sovereignty, Strategy, Lebanon Abstrak cKeamanan siber merupakan salah satu isu yang menarik perhatian dalam studi hubungan internasional. Isu ini menjadi penting tatkala hampir sebagian besar unsur kehidupan terhubung ke ruang siber. Penelitian ini berupaya menganalisis strategi keamanan siber Lebanon dalam dokumen resmi kemananan sibernya. Kerangka teori yang digunakan dalam dalam penelitian ini menggunakan Three Perspective Theory of Cyber Sovereignity yang menjelaskan pembagian lapisan dalam konteks kedaulatan di ruang siber. Metode yang digunakan ialah metode penelitian kuantitatif yang diperoleh melalui aplikasi MAXQDA dan GEPHI untuk memberikan bukti data dalam menganalisis dokumen strategi keamanan nasional Lebanon. Hasil penelitian ini menunjukkan bahwa dokumen strategi keamanan siber Lebanon cenderung bersifat eksklusif. Pemerintah Lebanon lebih dominan membahas hal-hal yang bersifat administratif, teoretis, prinsipil dan perencanaan. Kata kunci: Keamanan Siber, Kedaulatan, Strategi, Lebanon